2007
DOI: 10.1002/cne.21599
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant agouti‐related protein system in the hypothalamus of the anx/anx mouse is associated with activation of microglia

Abstract: Agouti-related protein (AgRP) is a key orexigenic neuropeptide expressed in the hypothalamic arcuate nucleus and a marker for neurons conveying hormonal signals of hunger to the brain. Mice homozygous for the anorexia (anx) mutation are characterized by decreased food intake, starvation, and death by 3-5 weeks of age. At this stage immunoreactivity for AgRP is increased in cell bodies but decreased in the nerve terminals. We studied when during early postnatal development the aberrant phenotype of the AgRP sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
33
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 88 publications
(117 reference statements)
5
33
0
Order By: Relevance
“…In addition, the canonical pathways generated in our microarray analysis suggest that cell death and inflammatory processes occur in the hypothalamus of the anx/anx mouse. This finding is in agreement with previous studies suggesting inflammation and cell death in the anx/anx hypothalamus (10,15,35,36). The anx locus is still unknown.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In addition, the canonical pathways generated in our microarray analysis suggest that cell death and inflammatory processes occur in the hypothalamus of the anx/anx mouse. This finding is in agreement with previous studies suggesting inflammation and cell death in the anx/anx hypothalamus (10,15,35,36). The anx locus is still unknown.…”
Section: Discussionsupporting
confidence: 93%
“…In the anx/anx mouse, the orexigenic AGRP system develops normally until P12, after which the normal, continuous increase in AGRP-ir fiber density in the main projection areas ceases, and in some areas even decreases. These changes overlap both temporally and spatially with activation of microglia (10) and expression of MHC class I gene (H2-D b ) by both neurons and glia cells (15). In addition, we have shown increased amounts of apoptotic cells and presence of activated caspase 6 in NPY-ir fibers in the hypothalamus of these mice, indicating degenerative processes (15).…”
supporting
confidence: 51%
See 2 more Smart Citations
“…Our findings echo the results of Lachuer et al (44), who found differential expression of several genes cytokines in anx/anx mice hypothalamus, and a recent neuropathological study that found activated microglia in several brain regions, supporting a CNS inflammation/neurodegeneration-associated process (54). Although the underlying mechanisms are unknown, glia can be activated after injury, releasing chemical mediators such as CNS cytokines.…”
Section: Hypothalamus Transcriptome Reveals Cachexia In Anx/anxsupporting
confidence: 91%